The Use of Image Media in Improving German Descriptive Writing Skills - Lusianti Barung; Syukur Saud; Muh. Anwar (Phonologie : Journal of Language and Literature, 2025)
Abstract. The aim of the research is to determine the planning, process and results of improving German Descriptive Writing Skills for SMA Negeri 11 Makassar Students using image media. This research is classroom action research consisting of two cycles or six meetings. The subjects of this research were all class XI students at SMAN 11 Makassar, consisting of 36 students. Research data was obtained through writing skills tests and participant observations carried out during the learning process. Based on the results of data analysis, it can be seen that an average score of 64.06 was obtained in cycle I and increased to 78.00 in cycle II. From the research results, it was concluded that students' German descriptive writing skills could be improved through the use of image mediaKeyword: Instructional Media, Image, writing skills, Descriptive, German language